Hepatitis E infection in patients with severe acute alcoholic hepatitis. (26th June 2014) - Haim‐Boukobza, Stéphanie; Coilly, Audrey; Sebagh, Mylène; Bouamoud, Mouna; Antonini, Teresa; Roche, Bruno; Yordanova, Olga; Savary, Janine; Saliba, Faouzi; Duclos‐Vallee, Jean‐Charles; Samuel, Didier; Ichai, Philippe; et al.
Abstract Background & Aims Hepatitis E virus (HEV) infection is a known cause of acute‐on‐chronic liver failure in developing countries, but its implication in Western countries remains unknown. HEV burden in the setting of severe acute alcoholic hepatitis (AAH) was assessed. Methods Patients admitted for severe AAH from 2007 to 2013, with available sera and histologically proven AAH, were included and managed according to current European guidelines. At admission, clinical and biological characteristics were collected; HEV serology and RNA detection were retrospectively performed. Results Eighty‐four patients were included. Mean age was 50.8 ± 9.6 years, 65.5% were male, 91.7% were cirrhotic and 33.3% presented with encephalopathy. Mean MELD and Maddrey scores were respectively 32.4 ± 11.4 and 73.3 ± 37. Liver biopsy showed mild, moderate and severe hepatitis in 25 (29.8%), 23 (27.4%) and 32 (38.1%) patients respectively. Steroids were given to 61 patients (72.6%) of whom 35 (57.4%) presented corticoresistance (mean Lille score: 0.78 ± 0.21). During hospitalization, 24 patients (28.6%) died and 11 (13.1%) were transplanted. Three patients (3.6%) presented markers of acute HEV infection and 21 (25%) markers of past HEV infection. Patient with acute infection were men, cirrhotic, and 2/3 presented with encephalopathy. Steroids were given to two patients without any response. The third patient died. None were transplanted. Conclusions A substantial proportion of patients with severe AAH had markers of acute HEV infection, with similar clinical presentation and outcomes. Larger studies are needed to evaluate HEV impact on AAH management, resistance to steroids, and outcome.